International nonproprietary names for biological and biotechnological drugs - V. V. Dudchenko; P. I. Popov; N. D. Bunyatyan; A. N. Yavorsky; V. A. Merkulov (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article presents generalized information about the program of the World Health Organization (WHO) related to International Nonproprietary Names (INN) of biological and biotechnological drugs. It reflects general principles for selecting INN for biological and biotechnological preparations, immunoglobulins (sera), preparations for gene therapy, glycosylated proteins and peptides, non-glycosylated proteins peptides and proteins, hybrid proteins, blood preparations, monoclonal antibodies, skin substitutes, transgenic products, vaccines, biosimilars. The conclusion was made about the need for an early solution to the global problem of assigning INN to biological and biotechnological drugs, while the number of authorized products remains relatively small.